Systematic review of the last 20 years of research on decentralized domestic wastewater treatment in Brazil: State of the art and potentials - Ferreira, Marcella Moretti [UNESP]; Fiore, Fabiana Alves [UNESP]; Saron, Alexandre; da Silva, Gustavo Henrique Ribeiro [UNESP] (IWA Publishing, 2021)
A DEWATS (decentralized wastewater treatment system) is an alternative for expanding sanitation. In Brazil, DEWATS is acknowledged by law and is part of the National Sanitation Plan strategy for achieving the treatment of 85.6% of all the generated wastewater by 2033, improving the current treatment index of 49%. This review's aim is to identify DEWATS studies in Brazil and to verify their potential for narrowing the national wastewater treatment deficit. Hence, aspects such as cost, maintenance, and efficiency were assessed. The archival research method (ARM) was used to identify papers published in the last 20 years through the scientific databases of Scopus, Science Direct, and Web of Science. Data regarding the general characteristics of each study were collected and compared to Brazilian environmental regulation and sanitation status. The results showed the evaluation of different technologies such as DEWATS, highlighting their flexibility and potential use in 79% of Brazilian counties. However, although 81% of the studies conducted performance analysis, none covered the main parameters required by Brazilian law. Although legal gaps for DEWATS improvement and consolidation have been identified and the interest in studying DEWATS has been increasing in the last five years, many barriers to their widespread use remain.
Keywords: Decentralized systems; Decentralized wastewater systems; DEWATS; Sanitation; Sanitation in Brazil; Wastewater treatment